2008
DOI: 10.1007/s11104-008-9784-0
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus runoff from a phosphorus deficient soil under common bean (Phaseolus vulgaris L.) and soybean (Glycine max L.) genotypes with contrasting root architecture

Abstract: The selection and breeding of crop genotypes with root traits that improve soil resource extraction is a promising avenue to improved nutrient and water use efficiency in low-input farming systems. Such genotypes may accelerate nutrient extraction ("nutrient mining"), but may also reduce nutrient loss via soil erosion by producing greater shoot biomass and by direct effects of root traits on aggregate formation and water infiltration. Little is known about the effects of root architecture on phosphorus (P) run… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 43 publications
0
13
0
1
Order By: Relevance
“…The remaining three-quarters of P lost in surface runoff came from topsoil either via dissolution or erosion of particles, and potentially, plant roots. However, Henry et al (2009) found that compared to soil P, root architecture did not affect the P concentration in surface runoff. Mundy et al (2003) added weight to the hypothesis that recently grazed material was a considerable source of P to runoff by showing about twice as much P was lost in outwash from flood irrigation of a pasture mown to 43 mm compared to uncut pasture.…”
Section: Introductionmentioning
confidence: 90%
“…The remaining three-quarters of P lost in surface runoff came from topsoil either via dissolution or erosion of particles, and potentially, plant roots. However, Henry et al (2009) found that compared to soil P, root architecture did not affect the P concentration in surface runoff. Mundy et al (2003) added weight to the hypothesis that recently grazed material was a considerable source of P to runoff by showing about twice as much P was lost in outwash from flood irrigation of a pasture mown to 43 mm compared to uncut pasture.…”
Section: Introductionmentioning
confidence: 90%
“…However, bean yields continue to be low in Central America, due to poor soil P availability [5]. Bean genotypes that can efficiently use soil P reserves have played a significant role in improving food security in this region [6]. Lynch [7] found that efficient bean genotypes have greater root mass, root length and root/shoot ratio, and their roots demonstrated an extraordinary ability to sense and respond to localized changes in P availability.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study the chlorophyll a+b content was found to be increased significantly in all treated plants as compared to FOP alone inoculated control. Previous reports suggested that applying biological control agents to infected plants increase mineral levels [(nitrogen (N), phosphorous (P), potassium (K) and magnesium (Mg)], chlorophyll biosynthesis and photosynthetic activity (Mahmoud et al, 2004;Henry et al, 2009;Morsy et al, 2009).…”
mentioning
confidence: 99%